Women and Natural Resource Management in the Rural North - Sloan, Lindis (Forlaget Nora, Kvinneuniversitetet i Nord. Website: http://www.kun.nl.no/, 2004)
The “Women and Natural Resource Management in the Rural North” project gives an account of women’s relationship with several resource-based industries and industrial developments in the Arctic Region, with fieldwork reports from Canada, Greenland, Iceland, Norway, Sweden amd Finland. The national projects include such diverse topics as the Canadian Hunters and Trappers organisations, Greenlandic mines, fisheries and the plans for a new aluminium plant in Iceland, the Norwegian oil and gas developments in the Barents Sea, hydropower in Sweden, and Finnish forestry. Women directly involved in the industries are interviewed, as are women living in areas where daily life is affected by the developments. Arctic Council's Sustainable Development Working Group